STUDY OF DIGITAL WALLET FEATURES AS A SUBSTITUTE FOR CASH IN PURCHASE DECISIONS IN THE MARKETPLACE - Aritonang, Natasya; Djumrianti, Desloehal; Elisa, Elisa; Afrizawati, Afrizawati (Jurnal Manajemen, 2025)
The study aims to determine and analyze the features of digital wallet services as a substitute for cash in purchasing decisions in the marketplace. This is a quantitative approach. Data was collected through a series of questionnaires with a sample size of 86 respondents. The sampling technique used Non-Probability Sampling, namely accidental techniques, for students who use Shopee and ShopeePay. Data analysis using simple linear regression analysis techniques with the help of SPSS (Statistical Package for the Social Sciences) version 25. The study shows that the t-test results on the service feature variable obtained a t-count of 11,051 at a significance level of 0.000 which indicates that the t-count of 11.051> t-table 1.989 and a significant value of 0.000 <0.05 which means that the service feature variable (X) partially has a positive and significant effect on purchasing decisions (Y).